Blood eosinophils and treatment response in hospitalized exacerbations of chronic obstructive pulmonary disease: A case-control study. (April 2016) - Serafino-Agrusa, Laura; Scichilone, Nicola; Spatafora, Mario; Battaglia, Salvatore
Abstract: Background: In outpatients with chronic obstructive pulmonary disease (COPD), blood eosinophilia is considered as a biomarker of response to systemic corticosteroid therapy. However, little is known on whether blood eosinophilia is also predictive of positive clinical outcome in severe acute exacerbations of COPD requiring hospitalization. We hypothesized that blood eosinophil-positive severe acute exacerbations of COPD differ from eosinophil-negative ones in terms of response to therapy and clinical outcomes. Methods: To test our experimental hypothesis, we retrospectively analyzed medical records of patients with COPD admitted to our ward because of severe exacerbation, over a two-year period of observation. After evaluation of inclusion and exclusion criteria, 132 patients were selected and divided in cases (blood eosinophilia ≥2% at admission; n = 20) and controls (blood eosinophilia <2% at admission; n = 112). Results: Cases had a shorter hospital stay than controls (geometric mean = 8.9 ± 1.5 versus 11.3 ± 1.5 days; p = 0.028). In addition, cases had a significantly lower consumption of systemic corticosteroids (geometric mean = 19.2 ± 4.0 versus 35.7 ± 2.5 mg per day of hospitalization; p = 0.012). Conclusions: In severe acute exacerbations of COPD requiring hospitalization, blood eosinophilia identifies a subgroup of subjects characterized by a prompt response to treatment with shorter hospital stay.